Treatment of patients waitlisted for liver transplant with all‐oral direct‐acting antivirals is a cost‐effective treatment strategy in the United States. Issue 1 (27th May 2017) - Ahmed, Aijaz; Gonzalez, Stevan A.; Cholankeril, George; Perumpail, Ryan B.; McGinnis, Justin; Saab, Sammy; Beckerman, Rachel; Younossi, Zobair M.
Abstract : All‐oral direct acting antivirals (DAAs) have been shown to have high safety and efficacy in treating patients with hepatitis C virus (HCV) awaiting liver transplant (LT). However, there is limited empirical evidence comparing the health and economic outcomes associated with treating patients pre‐LT versus post‐LT. The objective of this study was to analyze the cost‐effectiveness of pre‐LT versus post‐LT treatment with an all‐oral DAA regimen among HCV patients with hepatocellular carcinoma (HCC) or decompensated cirrhosis (DCC). We constructed decision‐analytic Markov models of the natural disease progression of HCV in HCC patients and DCC patients waitlisted for LT. The model followed hypothetical cohorts of 1, 000 patients with a mean age of 50 over a 30‐year time horizon from a third‐party US payer perspective and estimated their health and cost outcomes based on pre‐LT versus post‐LT treatment with an all‐oral DAA regimen. Transition probabilities and utilities were based on the literature and hepatologist consensus. Sustained virological response rates were sourced from ASTRAL‐4, SOLAR‐1, and SOLAR‐2. Costs were sourced from RedBook, Medicare fee schedules, and published literature. In the HCC analysis, the pre‐LT treatment strategy resulted in 11.48 per‐patient quality‐adjusted life years and $365, 948 per patient lifetime costs versus 10.39 and $283, 696, respectively, in the post‐LT arm. In the DCC analysis, the pre‐LT treatment strategy resulted in 9.27 per‐patient quality‐adjusted life years and $304, 800 per patient lifetime costs versus 8.7 and $283, 789, respectively, in the post‐LT arm. As such, the pre‐LT treatment strategy was found to be the most cost‐effective in both populations with an incremental cost‐effectiveness ratio of $74, 255 (HCC) and $36, 583 (DCC). Sensitivity and scenario analyses showed that results were most sensitive to the utility of patients post‐LT, treatment sustained virological response rates, LT costs, and baseline Model for End‐Stage Liver Disease score (DCC analysis only). Conclusion : The timing of initiation of antiviral treatment for HCV patients with HCC or DCC relative to LT is an important area of clinical and policy research; our results indicate that pre‐LT treatment with a highly effective, all‐oral DAA regimen provides the best health outcomes and is the most cost‐effective strategy for the treatment of HCV patients with HCC or DCC waitlisted for LT. (Hepatology 2017;66:46–56).